HEALTH SERVICES ASPECTS - ECONOMIC APPROACH - ALINA NIȚESCU (Annals of the University of Petrosani: Economics)
There is a constant concern for sustainable development. No investment can be made without analyzing the needs and determining the necessary resources, so that the result is the intended one. In this context, we must be aware that the most important resource, which has an active and decisive role in production and which enhances the other factors in order to obtain goods and services, is the human resource, human capital. Thus, the constant concern for the health needs of the population and the provision of quality medical services must be the priority of each state. Thus, this paper aims to highlight specific aspects of health services, approached from an economic perspective.